Deskripsi Kalimat Majemuk dalam Gambar Tampilan Blackberry Messenger Sebagai Bahan Ajar Pelajaran Bahasa Indonesia di SMP - Yunitamara, Shela, Prof. Dr. Markhamah, M.Hum (2016)
The research has three obbjective (1) to describe the type of compound sentence in the picture to see the BlackBerry Messenger, (2) to describe the use of conjunctions in complex sentence in the picture to see the BlackBerry Messenger, and (3) explain the benefits of conjunctions in the picture to see the BlackBerry Messenger as teaching materials in junior high. This research is a qualitative descriptive. The data in this study are the writings BalckBerry Messenger. The main data sources in this study are compound sentences in BlackBerry Messenger display picture. Methods of data analysis method used agih and unified method intralingual. Technic of data analysis used technic PUP and BUL. Data collection techniques refer to the method used in this study followed the techniques noted. The results showed 1) the type of compound sentence includes, (a) complex sentences storied, (b) complex sentences similar, 2) the use of conjunctions to form compound sentences in the picture to see the BlackBerry Messenger showed 8 types of relationships of meaning include (a) a conjunction because, for effect in relation to causation, (b) a conjunction so, then realize the relationship as a result, (c) conjunctions rather than to the relations of comparison, (d) conjunctions before, during realize the relationship of time, (e) conjunctions while realizing the relationships of meaning, (f) conjunction in order, so realizing relations purposes , (g) conjunctions and effect in relation to similar merge or summation, and (h) conjunctions but, but, but, instead of realizing the relationship equivalent resistance, and 3) Teaching materials from this study can be used as teaching materials Indonesian teachers education in particular junior class VII. Comptence base used is to understand Indonesia descriptive text responses through oral and written.